Formulasi serta Evaluasi Aktivitas Antioksidan dan Tabir Surya Secara in Vitro Pada Krim Ekstrak Etanol Daun Sukun (Artocarpus altilis) - Suradnyana, I Gede Made; Juli Widiarta, I Made; Yudianti Mendra, Ni Nyoman (Usadha, 2025)
Ultraviolet (UV) radiation exposure can cause various skin disorders, including sunburn, erythema, premature aging, wrinkles, pigmentation changes, and DNA damage, which may lead to photocarcinogenesis. Sunscreens play an important preventive role against these harmful effects, yet synthetic organic and inorganic agents may cause skin toxicity. Breadfruit (Artocarpus altilis) leaf extract contains phenolic compounds with dual photoprotective properties as antioxidants and UV filters. This study aimed to formulate and evaluate a sunscreen cream containing ethanol extract of breadfruit leaves. The formulation varied the concentrations of stearic acid and triethanolamine as emulsifiers. Physical properties (organoleptic, homogeneity, pH, adhesion, and spreadability) and in vitro activities (antioxidant by DPPH method and SPF by spectrophotometry) were assessed and compared with commercial creams. The results showed that the cream formulation containing 4% stearic acid and 2% triethanolamine exhibited the most ideal physical characteristics compared to commercial products. The breadfruit leaf ethanol extract cream demonstrated weak to moderate antioxidant activity, while at a concentration of 400 ppm, it exhibited sunscreen protection categorized as maximum protection. The ethanol extract of breadfruit leaves has the potential to be developed into a natural sunscreen formulation that is safe and environmentally friendly.